Hold Nothing Back : Writings by Dorothy Day - Day, Dorothy, 1897-1980 (Book collections on Project MUSE., 2016)
Dorothy Day (1897-1980) was a well-known American journalist, activist, and Catholic convert whose cause for sainthood has been endorsed by the US bishops. She wrote numerous articles over a period of several decades for the prominent lay Catholic magazine Commonweal. 'Hold Nothing Back' is gleaned from those writings. It includes reflections on her life as a single mother, her time in jail for civil disobedience, her struggles to keep the Catholic Worker movement she cofounded afloat, and her travels on crowded buses to report from the front lines about labor disputes, racial inequality, and poverty. At the heart of whatever Day wrote lies a profound and prophetic faith. 'Hold Nothing Back'--a new, abridged edition of the previously published 'Dorothy Day: Writings from Commonweal'--gives a glimpse of her remarkable humanity and endurance, and of the vibrant spirituality that underlay them. (Publisher).